SOSIALISASI PENYUSUNAN LAPORAN KEUANGAN UMKM BERDASARKAN SAK EMKM PADA ANGGOTA KOMUNITAS KETRAMPILAN PEREMPUAN TLOGO KREASI DI KELURAHAN TLOGOSARI KULON KOTA SEMARANG - Ratna Wijayanti; Suratman Suratman; Eviatiwi Kusumaningtyas Sugiyanto (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2020)
The Tlogo Kreasi Women's Skill Community, Tlogosari Kulon Village, is an SMME that stands based on the hobbies of some housewives in making crafts, and then traditionally sold between friends and local residents, though the community is getting bigger, they do not have the knowledge about proper financial management. This background, the community service team will encouraged their understanding and knowledge about how to prepare financial reports based on SAK EMKM, so they will understand and be able to apply proper financial reporting. The approach used in this case is a participatory training approach, through outreach and workshops. The material for this financial report based on the needs of the community who do not really understand the importance of financial reports as a support to the progress of community development. The results of this service are increased participant understanding and skills in making financial reports based on SAK EMKM.